2016
DOI: 10.3390/w8070279
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Validation of Cisco Lethal Conditions in Minnesota Lakes under Past and Future Climate Scenarios Using Constant Survival Limits

Abstract: Fish habitat in lakes is strongly constrained by water temperature (T) and available dissolved oxygen (DO) that are changed under climate warming. A one dimensional, dynamic water quality model MINLAKE2012 was used for T and DO simulation over 48 years. A fish habitat model FishHabitat2013 using simulated T and DO profiles as input was developed to determine lethal conditions of cisco Corgenous artedi in Minnesota lakes. Twenty-three lakes that had observations of cisco mortality or survival in the unusually w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Contour plots of a total number of years with cisco kill under future MIROC3.2 climate scenario from Jiang and Fang's study [11]. Duluth weather data were used for model simulations, and contours were derived by interpolation from simulated points for (a) 12 shallow and 16 mediumdepth virtual lakes, and (b) 30 deep virtual lakes.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Contour plots of a total number of years with cisco kill under future MIROC3.2 climate scenario from Jiang and Fang's study [11]. Duluth weather data were used for model simulations, and contours were derived by interpolation from simulated points for (a) 12 shallow and 16 mediumdepth virtual lakes, and (b) 30 deep virtual lakes.…”
Section: Figurementioning
confidence: 99%
“…The H max of the 620 cisco lakes ranges from 3.0 to 64.9 m [29], whereas H max of the 30 deep virtual lakes is 24 m; therefore, only using the contour lines of AvgATDO3 simulated from deep lakes to classify the refuge lakes may not be accurate for shallower lakes. Jiang et al [11] used constant survival limits of T and DO (i.e., lethal temperature and DO limit for cisco) to study the "total number of years with cisco kills" (Figure 4) and the "average cisco kill days for the years with kills" of three different types of virtual lakes (shallow H max = 4 m, medium-depth H max = 13 m, and deep H max = 24 m) and found that above two simulated variables have a big jump from shallow and medium-depth virtual lakes to deep virtual lakes. This further indicates that, to better represent 620 cisco lakes, more types of virtual lakes need to be used for developing contour lines of AvgATDO3 and then classifying refuge lakes.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations